2020
DOI: 10.1177/1359105320946358
|View full text |Cite
|
Sign up to set email alerts
|

Role of resilience and emotional control in relation to mental health in people with cancer

Abstract: This study explored the relationship between emotional control, resilience, and mental health in cancer. Patients with cancer were recruited ( n = 170). Courtauld Scale of Emotional Control, Connor-Davidson Resilience Scale, and the General Health Questionnaire were selected. Assuming the absence of interaction among the variables, they were analyzed separately. Four groups resulted, finding statistically significant differences ( F(4, 165) = 18.03; p < 0.001). High resilience and low emotional control seem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
2
7
1
Order By: Relevance
“…This finding confirms a long tradition of cancer health studies emphasizing the fundamental role of resilience as a protective factor against the risk of developing adverse health outcomes [ 14 16 ]. Notably, our findings are consistent with those recently reported by Groarke et al [ 41 ], who found that resilience moderates the relationship between stress and distress, and that the effects of masculine identity threat on adjustment diminish in the face of resilience [ 42 ]. However, in the current study, we only examined the individual characteristics of the construct, whereas there are several factors that contribute to the cancer patient’s resilience and thus mental health, including biological and social (e.g., social support) factors [ 43 ].…”
Section: Discussionsupporting
confidence: 93%
“…This finding confirms a long tradition of cancer health studies emphasizing the fundamental role of resilience as a protective factor against the risk of developing adverse health outcomes [ 14 16 ]. Notably, our findings are consistent with those recently reported by Groarke et al [ 41 ], who found that resilience moderates the relationship between stress and distress, and that the effects of masculine identity threat on adjustment diminish in the face of resilience [ 42 ]. However, in the current study, we only examined the individual characteristics of the construct, whereas there are several factors that contribute to the cancer patient’s resilience and thus mental health, including biological and social (e.g., social support) factors [ 43 ].…”
Section: Discussionsupporting
confidence: 93%
“…Conversely, Emotional Control and Social Support did not show any influence over mental health perception. These results contradict what other studies have found, which have considered the relevance of high perceived social support and emotional expression (opposite to emotional control) as factors related to positive health outcomes in cancer ( Durá et al, 2010 ; Costa-Requena et al, 2014 ; Li et al, 2015 ; Macía et al, 2020b ). In particular, absence of effect of social support over mental health is remarkable in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…Psychological interventions should emphasize the increase of aspects such as resilience and extraversion in patients, through specific techniques focused in group-based sharing processes, resilience building interventions (increase of like self-esteem, cognitive flexibility, connectedness with significant others), development of therapeutic alliance and confidence, etc. ( Solano et al, 2016 ; Reynolds, 2019 ; Macía et al, 2020b , c ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study show a significant and positive correlation between evasive coping and resilience, as well as a negative correlation between emotive coping subscale and resilience. These results are in line with other studies who found a significant and negative relationship between the use of emotion-oriented coping and resilience among diabetic adolescents (Macía et al, 2020;Messinger, 2017). The results of other studies indicated that evasive coping is negatively related to resilience, which was not in line with the present study results (Chen et al, 2018;Thompson et al, 2018).…”
Section: Discussionsupporting
confidence: 93%